Analysis of the status of provision of pharmaceutical care to patients with multiple sclerosis in Ukraine - Tkachenko, N. O.; Ryzhkova, S.; Olkhovska, A.; Ткаченко, Наталя Олександрівна (My University, 2025)
Considering modern approaches to the treatment of chronic non-communicable diseases, as well as the experience of active involvement of pharmacists in multidisciplinary teams of healthcare professionals, it is relevant to determine the professional role of a pharmacist in teams providing medical and social care to patients with multiple sclerosis (MS). The aim: to analyze the state of pharmaceutical care (PC) provision to Ukrainian patients with multiple sclerosis (MS). Materials and methods. The study is based on scientific works of domestic and foreign researchers on this problem, regulatory documents on the provision of medical care to patients with MS and the results of a sociological survey of patients diagnosed with MS. The study used methods of scientific information search, narrative approach, generalization, survey, statistical analysis, and others. Results. The pharmaceutical component of the medical care process was determined and a list of drugs used in the complex therapy of MS was determined: H02AB – glucocorticoids, L01BB – structural purine analogues, L01FA – CD 20 inhibitors, L03AB – interferons, L04AA – selective immunosuppressants, L04AG – monoclonal antibodies, L04AX – other immunosuppressants. The analysis of the availability of DMT drugs showed that only 75% of the recommended drugs are physically available in Ukraine, with drugs with lower efficacy prevailing. The low availability of highly effective drugs (drugs) of the 3rd category for Ukrainian patients with MS is due to the lack of state funding for their purchase, which makes treatment with such drugs financially burdensome for patients. The survey found that 64.5% of patients would like to receive additional support from pharmacists. Possible elements of pharmaceutical care that are important for patients with MS were identified, such as counselling, coordination with public organizations, explanation of new treatment options, and symptom monitoring. When assessing patients’ adherence to PC, factors such as age, gender, location, displaced status, work restrictions, or time since diagnosis did not significantly influence patients’ positive attitudes. Furthermore, these factors did not influence patients’ preferences for preferred pharmacist interaction format (face-to-face, mixed, or telepharmacy). Conclusions: There is a need to expand the availability and update the registration of drugs for the treatment of MS. Patients with MS have a positive attitude towards pharmaceutical care, but need more awareness of its possibilities. Social status affects the perception of the need for pharmaceutical care and the choice of the format of its provision.
Keywords: multiple sclerosis; pharmaceutical care; drugs; pharmacist